Application of Transcranial Magnetic Stimulation to Improve Upper Limb Motor Function Following Cerebral Infarction: A Clinical Case Analysis - Greta Gimbutaitė; Paulina Stočkūnaitė; Laura Petrusevičienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Cerebral infarction, a form of acute cerebrovascular disorder affecting the brain or spinal cord, presents with focal neurological symptoms that persist for more than 24 hours post-onset. Managing complications arising from cerebral infarction typically involves a multifaceted and prolonged therapeutic approach. Recent advancements, such as the application of transcranial magnetic stimulation (TMS), have shown the potential to significantly accelerate the rehabilitation process by enhancing neuroplasticity and motor recovery.